A rare case report on unilateral cranial nerve palsy (9th and 10th) with skull base osteomyelitis (Indian Journal of Case Reports, 2020)
Skull base osteomyelitis (SBO) is a rare disease affecting predominantly diabetic and immunocompromised adults and has a high mortality rate of about 10–20%. Here, we describe the case of SBO with progressive cranial nerve palsy involving 9th and 10th cranial nerves in a 30-year-old female patient who presented with a history of dysphagia and nasal regurgitation of food. The patient had no weakness and ataxia but over the following weeks, she developed 9th and 10th cranial nerve palsy. Magnetic resonance imaging brain report shows SBO and the patient was started on i.v. antibiotics. After which, the patient responded to treatment. SBO is a life-threatening condition and prolonged administration of antibiotics is a valuable option among these patients.